Authentication of Three Source Spices of Arnebiae Radix Using DNA Barcoding and HPLC - Xu, Haiyan; Li, Ping; Ren, Guangxi; Wang, Yanjiao; Jiang, Dan; Liu, Chunsheng (Frontiers in Pharmacology, 2021)
Arnebia decumbens (Vent.) Coss. et Kralik, A. euchroma (Royle) Johnst and A. guttata Bunge, three commonly used traditional Chinese medicinal plants have been widely used for the clinical treatment of inflammatory diseases caused by fungal, bacterial, oxidation and other related pathogens. However, precise identification at the similar species level is usually challenging due to the influence of the source of medicinal materials, traditional ethnic medicine and medicinal habits. Here we developed a comprehensive and efficient identification system for three source spices of Arnebiae Radix based on DNA barcoding and HPLC fingerprinting. A total of 599 samples from thirty-five wild populations were collected and identified by using DNA barcodes of ITS2 regions, and the chemotypes of 7 naphthoquinoneswere revealed by HPLC quantitative analysis including principal component analysis and hierarchical clustering analysis. Our results showed that the ITS2 sequences can distinguish three source spices of Arnebiae Radix from adulterants. However, it was difficult to identify them by HPLC-specific chromatograms combined with chemometric analysis. These results indicated that DNA barcoding was a more powerful method than HPLC fingerprinting for the identification of related species that were genetically similar. DNA barcoding analysis could be a promising and reliable tool to accurately confirm the identities of medicinal materials, especially for those whose sources are multiple and difficult to be identified by conventional chromatography.